Nimodipine protects Schwann and neuronal cells from cell death induced by cisplatin without affecting cancer cells - Leisz, Sandra; Fritzsche, Saskia; Strauß, Christian; Scheer, Maximilian; Scheller, Christian (Scientific reports, 2025)
Cisplatin is a well-established drug for the treatment of solid tumors. One of the most common side effects is neurotoxicity and peripheral neuropathy, which affects patients’ quality of life. In previous studies, a protective effect of nimodipine on neuronal cell stress was demonstrated. Therefore, the objective of this study was to examine the impact of nimodipine on cisplatin-treated Schwann cells, neuronal cells, and tumor cells. Schwann and neuronal cells were used to investigate the neuroprotective effect of nimodipine, as well as the cancer cell lines A549, SAS and SKOV-3 to determine the effect on tumor cells. Cell death was measured using extracellular lactate dehydrogenase activity and propidium iodide staining. In addition, the protein level of the LIM-domain only four protein and the activation of known interacting anti-apoptotic pathways were analyzed. The cytotoxic effect of cisplatin was reduced by up to 23.6% in neuronal cells (p ≤ 0.0001) and up to 30.6% in Schwann cells (p ≤ 0.05) by nimodipine pre-treatment. However, no decrease in apoptosis could be shown in the cancer cells. Nimodipine-dependent activation of anti-apoptotic signaling pathways was detectable in Schwann cells and neuronal cells, whereas the opposite effect could be demonstrated in the cancer cells. In conclusion, the treatment with nimodipine may represent a new approach against neurotoxically side effects in cisplatin chemotherapy.
Veröffentlicht: 25. Juni 2025